Role of trichoscopy in evaluation of alopecia areata: A study in a tertiary care referral centre in the eastern India - Vineet K Sahu; Adrija Datta; Tanusree Sarkar; Tirthankar Gayen; Gobinda Chatterjee (Wolters Kluwer Medknow Publications, 2022)
Background: Alopecia areata is an autoimmune disorder affecting the hair-bearing sites of the body. Trichoscopy has recently been practiced in the diagnosis of alopecia areata. Aim: To elicit trichoscopy patterns in alopecia areata and to find out any correlation of trichoscopic findings with disease severity. Methods: Trichoscopy was done on clinically diagnosed cases of alopecia areata and on age and sex-matched controls without hair disorders by using a DL1 dermoscope (magnification: ×10). Observed dermoscopic findings were analyzed to find the correlation with disease severity. Results: In total, 87 cases and 60 controls were included in the study with the mean age for cases being 25.47 ± 14.07 years. There was male predominance of cases (51; 58.62%). Alopecia in multiple patches was the most common type (42; 48.27%), and scalp was the most common site of involvement (79; 90.8%). Yellow dots (YD), black dots (BD), broken hairs (BH), circle hair (CH), and tapering hairs (TH) or exclamation hair (EH) were found to be statistically significant findings in alopecia areata as compared to controls. Circle hair was significantly associated with total severity of alopecia areata (P = 0.041). Yellow dots had a positive correlation with the number of episodes of alopecia areata (Spearman's rho = 0.273, P = 0.0106) and mean severity of alopecia tool (SALT) score (P = 0.0130). No significant association was noted between trichoscopic findings and disease activity, family history, disease associations, or nail involvement. Conclusion: A constellation of trichoscopic findings helps in establishing the diagnosis of alopecia areata obviating the need for biopsy.